Robotic-Based Learning Media in Islamic Education: Validity, Practicality, and Effectiveness in Primary School - Herawati, Anisa; Mu'ammar, Muhammad Arfan; Arifin, Zainal (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study aims to develop a Tawaf Robot learning media and to examine its feasibility and effectiveness on the learning outcomes of second-grade students at Muhammadiyah 6 Elementary School, Surabaya, in the subject of Islamic Religious Education. Using the Research and Development (R&D) method, the writers aim to investigate the following questions: how does the development of the Tawaf Robot media enhance the learning motivation of second-grade students, and what are the outcomes of the media? The posttest results show a significant increase in scores, with an average of 93.7, indicating a more thorough understanding through the media than with conventional learning methods. The main advantage of using the Tawaf Robot Media is its ability to attract students’ interest and to design a more interactive learning experience. It can be concluded that the Tawaf Robot, when used as a learning medium, meets the criteria of validity, practicality, and effectiveness in learning.